2021
DOI: 10.1155/2021/9924542
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Treatment Experience in Severe and Critical COVID-19

Abstract: Compared with other deadly diseases, the coronavirus disease 2019 (COVID-19) is highly infectious with a relatively low mortality rate. Although critical cases account for only 5% of cases, the mortality rate for the same is nearly 50%. Therefore, the key to the COVID-19 treatment is to effectively treat severe patients and reduce the transition from severe to critical cases. A retrospective study was carried out to evaluate outcomes of treatment in patients with severe and critical COVID-19 admitted to a COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…In severe cases of COVID-19, increased oxidative stress can lead to inflammation, damage to endothelial cells, and blood clots, which can damage multiple organs. Moreover, SARS-CoV-2 can cause oxidative stress, interfering with inflammatory pathways and potentially cause long-term tissue harm [51,52].…”
Section: Oxidative Stress Plays a Crucial Role In Covid-19 Infectionmentioning
confidence: 99%
“…In severe cases of COVID-19, increased oxidative stress can lead to inflammation, damage to endothelial cells, and blood clots, which can damage multiple organs. Moreover, SARS-CoV-2 can cause oxidative stress, interfering with inflammatory pathways and potentially cause long-term tissue harm [51,52].…”
Section: Oxidative Stress Plays a Crucial Role In Covid-19 Infectionmentioning
confidence: 99%
“…COVID-19 is highly infectious. 2 It has now developed into a global pandemic, affecting more than 214 countries and regions around the world. As of July 2021, the cumulative number of confirmed cases worldwide has exceeded 190 million, and the cumulative number of deaths has exceeded 4 million.…”
Section: Introductionmentioning
confidence: 99%
“… 12 26 The period of 1 month seems reasonable since previous studies reported the time from symptom onset to diagnosis to be as long as 4 weeks. 54 55 …”
Section: Discussionmentioning
confidence: 99%